Towards an Integrated Land and Water Resources Management in Brandenburg’s Oderbruch-Havelland Wetland Belt: History and Strategies for the Future - Quast, Joachim (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
The article informs about historical developments and recent problems in the former wetlands of the Oderbruch, which has been cultivated for agricultural use for 300 years, and in the fen region of the Rhin-Havel-Luch. The periodically inundated floodplains of Oderbruch are characterised by rich-in-clay sedimentation soils, while Rhin-Havel-Luch is a year-round wet fen region with peat soils. In both areas land use necessarily requires an adequate regional water management, employing measures and system solutions for river training, dike construction, drainage and soil cultivation. Options for action and adaptation strategies for the next 20 to 40 years, based on many years of own analyses and case studies, are presented and discussed. The article also considers an aggravation of the problems to be expected from climate change.